1997
DOI: 10.1136/bjo.81.5.350
|View full text |Cite
|
Sign up to set email alerts
|

Variation of nerve fibre layer thickness measurements with age and ethnicity by scanning laser polarimetry

Abstract: Aims-Scanning laser polarimetry is a new technique allowing quantitative analysis of the retinal nerve fibre layer in vivo. This technique was employed to investigate the variation of the retinal nerve fibre layer thickness in a group of normal subjects of diVerent ages and ethnic groups. Methods-150 normal volunteers of different ages and ethnic groups were recruited for this study. Three consecutive 15 degree polarimetric maps were acquired for each subjects. Nerve fibre layer thickness measurements were obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
125
10
1

Year Published

1998
1998
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(152 citation statements)
references
References 22 publications
15
125
10
1
Order By: Relevance
“…Crosssectional studies of RNFL thickness using scanning laser polarimetry also have found a decrease in RNFL thickness with age. [9][10][11][12] The human RNFL loses approximately 5000 axons per year from birth to death, approximately 2500 per year before age 50 and 7500 per year after 50. 3 It is not surprising, then, that RNFL thickness decreases with age.…”
Section: Discussionmentioning
confidence: 99%
“…Crosssectional studies of RNFL thickness using scanning laser polarimetry also have found a decrease in RNFL thickness with age. [9][10][11][12] The human RNFL loses approximately 5000 axons per year from birth to death, approximately 2500 per year before age 50 and 7500 per year after 50. 3 It is not surprising, then, that RNFL thickness decreases with age.…”
Section: Discussionmentioning
confidence: 99%
“…The details of this technique have been described previously. 12,13 A total of 65 536 retinal locations were measured to create a retardation map corresponding to RNFL thickness over a 151 (256 Â 256 pixel) retinal area. While undergoing scanning, the mean pupil diameters of the normal subjects were 2.870.3 mm and the mean pupil diameters of patients with AACG were 5.071.2 mm.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, intersubject variation of NFLT, overlapping of NFLT between normal eyes and glaucomatous eyes, 1 and decrease in NFLT with aging 5,19,20 may make the study even more difficult. Therefore, in this study we selected patients with abnormalities localized either to the upper or to the lower hemifield, and compared NFLT measurements in the corresponding normal hemifield to evaluate the changes in NFLT before the development of visual field loss in glaucomatous eyes.…”
Section: Discussionmentioning
confidence: 99%